HUBUNGAN MINAT BELAJAR KEJURUAN DAN PRESTASI BELAJAR PRAKTIK PENGELASAN DENGAN MINAT BEKERJA DI INDUSTRI SISWA KELAS XI SEMESTER GENAP TEKNIK PENGELASAN SMK NEGERI 1 SEDAYU BANTUL YOGYAKARTA TAHUN AJARAN 2014/2015 - Nanda Pratama; Setuju Setuju (Jurnal Taman Vokasi, 2015)
This study aimed to describe (1) correlation vocational learning interest with working interest in industry among the eleventh grade students of SMK Negeri I Sedayu Bantul Yogyakarta in the academic year 2014/2015; (2) correlation learning achievement of welding practice subject with working interest in industry among the eleventh grade students of SMK Negeri I Sedayu Bantul Yogyakarta in the academic year 2014/2015; and (3) correlation vocational learning interest and learning achievement of welding practice subject with working interest in industry among the eleventh grade students of SMK Negeri I Sedayu Bantul Yogyakarta in the academic year 2014/2015. This study was ex-post facto. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double regression with two predictors. This study shows that (1) there was a positive and significant correlation vocational learning interest with working interest in industry among the eleventh grade students of SMK Negeri I Sedayu Bantul Yogyakarta in the academic year 2014/2015 with the significant score 0.007 < 0.05; (2) there was a positive and significant correlation learning achievement of welding practice subject with working interest in industry among the eleventh grade students of SMK Negeri I Sedayu Bantul Yogyakarta in the academic year 2014/2015 with the significant score 0.000 < 0.05; and (3) there was a positive and significant correlation vocational learning interest and learning achievement of welding practice subject with working interest in industry among the eleventh grade students of SMK Negeri I Sedayu Bantul Yogyakarta in the academic year 2014/2015 with the significant score 0.000 < 0.05. The score of determinant coefficient (R2) was 0.127, it means that learning interest and learning achievement of welding practice subject gave contribution 12.7% toward working interest in industry, while 88.3% was influenced by other factors.Â